KOMPETENSIYA YONDASHUVI ASOSIDA TALABALARNING TEXNIK VA TEXNOLOGIK TAYYORGARLIGINI SHAKLLANTIRISH - Orınbetov, N.; Amanbaev, M.; Allamuratova, Х. (SCIENCE and SOCIETY, 2024)
The article discusses the formation of technical and technological readiness of students based on the competence approach, and analyzes the main directions of applying artificial intelligence (AI), robotics and digital technology tools to the educational process in the formation of technical and technological readiness of students and recommendations are given on effective use of social networks.
Keywords: modern technology and tools; modern laboratories; equipment and software; technical and technological training; artificial intelligence; cyber security; robotics; distance education; online platform; digital technology; virtual laboratory and simulator; modern equipment hardware; software and technology